New trends in vibration based structural health monitoring - Deraemaeker, Arnaud 1974-; Worden, Keith (CISM Courses and Lectures, 2010)
This book is a collection of articles covering the six lecture courses given at the CISM School on this topic in 2008. It features contributions by established international experts and offers a coherent and comprehensive overview of the state-of-the art research in the field, thus addressing both postgraduate students and researchers in aerospace, mechanical and civil engineering